Faith Matters: From a Disability Lens. (3rd July 2017) - Tillotson, Nicole; Short, Monica; Ollerton, Janice; Hearn, Cassandra; Sawatzky, Bonita
ABSTRACT: In this article, the authors engage with matters of faith as expressed by Christians living with disabilities, recognizing faith matters to many. Extant debates regarding faith and disability risk being about people living with disabilities rather than being by or with them. This article presents a cooperative inquiry about faith undertaken by five Christian women, three of whom identify as living with disabilities, who explored their own and collective expressions of faith. Each outlines her intimate experience of faith and critically reflects on the norms and values informing her Christian worldview. Additionally, the authors summarize the inquirers' perceptions regarding Christian churches and inclusion.